Quality of pharmaceutical care service on patient satisfaction in the government health sector in the Kingdom of Saudi Arabia - Al-Khathlan, Muhammad Saud; Al-Turki, Turki Abdel Aziz; Al-Afnan, Anwar Ibrahim; Al-Zoghaibi, Bandar Abdullah; Al-Mutairi, AbdulRahman Zabin; Bagader, Ibrahim Mohamed; Abdo, Raghad AbdelKarim; Al-Dosari, Safia Mohammed; Al-Mutairi, Abdullah Zabin; Al-Jareed, Wafaa Daoud; Al-Haidan, Youssef Saleh (Arab Journal for Sciences and Research Publishing, 2022)
The study aimed to identify the quality of the pharmaceutical care service on patient satisfaction in the government health sector in the Kingdom of Saudi Arabia, and to find the correlation between the quality of the pharmaceutical care service and patient satisfaction in the government health sector in the Kingdom of Saudi Arabia. The research community included patients benefiting from pharmacies in government hospitals in Riyadh in the year 1444 AH, and the study sample consisted of (210) patients who were selected by a simple random sampling method. The study used a questionnaire as a tool for data collection. In light of the foregoing, the study reached a number of results, the most important of which is the existence of a positive relationship with statistical significance between the quality of the pharmaceutical care service and patient satisfaction in the government health sector in the Kingdom of Saudi Arabia. In light of the results, the study recommends the need to develop an effective system for receiving patient complaints that ensures rapid response and treatment to achieve continuous communication between them and the pharmacy management, or to activate the complaints boxes in the pharmacy and notify patients of dealing with the complaints they submit. The necessity of breaking the barrier between the pharmacist and patients, creating the language of dialogue, and recommending the medical staff not to speak with patients a foreign language that they do not understand.